PEMANFAATAN EKSTRAK BUAH GENDOLA (BASELLA RUBRA LINN) SEBAGAI BAHAN ALTERNATIVE DETEKSI PLAK GIGI (UJI INVITRO) - Ani Subekti; Nurul Kusuma Wardani; Erni Mardiati (Jurnal Kesehatan Gigi, 2018)
TITLEUTILIZATION OF FRUIT EXTRACT GENDOLA (BASELLA RUBRA LINN) AS AN MATERIAL  OF ALTERNATIVE DETECTION PLAQUE ( INVITRO TEST)ABSTRACTGendola fruit (Basella Rubra Linn) is one of the fruits that contain anthocyanin (red dye). In dental hygiene, to see the plaque necessary dyes whose color contrasts with the color of teeth. The material often used to see the plaque is Disclosing solution. The purpose of this study was conducted to test the in vitro gendola fruit extracts as an ingredient of plaque detection.This type of research was Experimental Research. The research design used was Posttest Only Control Group Design. The sample was 32, as many as 16 teeth spilled with a few drops of  extracts of fruit gendola, and as many as 16 teeth spilled with Disclosing solution. Prior spilled fruit extracts gendola, the teeth soaked in saliva for 6 hours. Statistical analysis of test data used independent t-test.Results of research by independent t-test test showed that value of significancy 0.08 (p 0.05), which means that the  gendola fruit extract has least the same ability with disclosing solution to detect the presence of plaque. The Gendola fruit extracts can be used  as an alternative to detect of plaque by a simple.